(untitled) (Global Journal of Science Frontier Research, 2023)
In this article a solution is proposed for several questions that have been facing modern Earth Science for a long time The questions of Earth s magnetic field physics mountain formation oceanic currents tides earthquakes geodynamics and other natural phenomena caused by the influence of external gravitational forces are considered A different view of the underlying physics allows for an easy and well-argued explanation of many natural phenomena making it understandable even to unprepared readers This view when applied to other planets can help in explaining other phenomena in the Solar System It is hoped that the scientific community will adopt this new explanation as a tool for further investigation of nature Any constructive criticism on the topic is welcome